Leadership in Higher Education - Kouzes, Jim; Posner, Barry; Safari, an O'Reilly Media Company (Berrett-Koehler Publishers, 2019)
The authors of the classic bestseller The Leadership Challenge bring their expertise to higher education, offering five practices that can make any college or university leader into an exemplary leader. Drawing on the same pioneering research that formed the foundation of their classic bestseller The Leadership Challenge (over 2.7 million copies sold), James Kouzes and Barry Posner offer a set of leadership skills and practices that will make a significant difference in every area of higher education-faculty, administration, library services, career counseling, auxiliary services, campus safety, and more. It's about the behaviors that leaders, regardless of their position, use to transform values into actions, visions into realities, obstacles into innovations, segments into solidarity, and risks into rewards. Kouzes and Posner tell the leadership story from the inside and move outward, describing it first as a personal journey and then as mobilizing others to want to do things they have never done before. The Five Practices of Exemplary Leadership is the operating system for this adventure. Leadership in Higher Education explains the fundamental principles that support these practices and provides case examples of people in higher education who demonstrate each one. A core theme that weaves its way through all the chapters is that, whether it's one to one or one to many, leadership is a relationship between those who aspire to lead and those who choose to follow. We need leaders who can unite us and ignite us. This book lights the way.
Made available through: Safari, an O'Reilly Media Company.
Online resource; Title from title page (viewed September 17, 2019).
eBooks on EBSCOhost
Keywords: Educational leadership; Education, Higher -- Aims and objectives; Universities and colleges -- Administration; Universities and colleges -- Business management; Leadership en éducation.; Enseignement supérieur -- Finalités.; Universités -- Administration; Universities and colleges -- Business management; Education, Higher -- Aims and objectives; Educational leadership; Universities and colleges -- Administration